A study on properties of chitosan-PEO electrolyte containing europium salt - Alves, Raquel Diana Carneiro (2017)
Chitosan and poly(ethylene oxide) (PEO) powders were mixed in different ratios, and a fixed amount of europium triflate and glycerol were added to each mixture. The properties of these samples were studied by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), X-ray diffraction (XRD), and complex impedance spectroscopy. TGA revealed that the electrolytes are stable up to 145ºC. The samples’ morphology and structure are homogeneous, and a presence of small crystalline peaks in some XRD may be related to the salt that probably is not totally accommodate in the blended matrix. The best ionic conductivity values of 1.92x10-8 S cm-1 at 30ºC was registered for the sample with 50:50 composition.